Larvicidal property of the extracts of the seaweeds; Sargassum wightii, S. ilicifolium and Gelidiella acerosa against Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus. (August 2022) - Perumal, Pachiappan; Dhanasundaram, Sundaramoorthy; Aravinth, Annamalai; Amutha, Vadivel; Santhanam, Perumal
Abstract: Toxicity potential of the 3-solvent extracts of Sargassum wightii, S. ilicifolium and Gelidiella acerosa – seaweeds against the 4th larval-stage of 3 mosquitos was evaluated. The ethyl acetate extracts of the brown seaweeds ( S. wightii & S. ilicifolium ) and the red seaweed ( G. acerosa ) exerted the highest larvicidal effect. The S. wightii -ethyl acetate extract (SW-EA) exerted the huge mortality rates in Anopheles stephensi with the (LC50 ) values (μg/mL) of 3.98 followed by 4.43 on Culex quinquefasciatus and 9.26 on Aedes aegypti . The extracts of S. ilicifolium - ethyl acetate (SI-EA) caused the mortality of An. stephensi with the lethal concentrations (LC50 ) values (μg/mL) of 18.93 followed by 34.10 on Ae. aegypti, and 40.73 on Cx. quinquefasciatus . The corresponding lethal concentrations (LC50 ) values for the G. acerosa -ethyl acetate-extract (GA-EA; that caused maximum death-toll of An. Stephensi ) were; 4.59 followed by 14.18 on Cx. quinquefasciatus and 23.26 on Ae. aegypti . The phytochemical, FTIR and GC-MS - analyses of the algal-extracts revealed the presence of common phytochemicals, the possession of aliphatic amines, alkynes and alkenes and the predominance of the Phytol acetate, Octadecanoic acid and n-Hexadecanoic acid. The generated data form the important basis for further investigation towards antimalarial drug development, in future. Graphical abstract: Image 1 Highlights: The mosquito-larvicidal effects of the extracts of the seaweeds; Sargassum wightii, S. ilicifolium and Gelidiella acerosa, collected from the Southeast India, were evaluated. The seaweeds-ethyl acetate-extracts have exerted highest lethality on the larvae of An. stephensi, Ae. aegypti and Cx. quinquefasciatus . The seaweeds-extracts were found to possess important compounds like, Phytol acetate, Octadecanoic acid and n-Hexadecanoic acid.